Efficacy of Assessment of Respiratory Risk in Surgical Patients in Catalonia (ARISCAT) Score Versus Local Assessment of Ventilatory Management During General Anesthesia for Surgery (LAS VEGAS) Score in Predicting Postoperative Pulmonary Complications in Abdominal Surgeries: A Comparative Study - Khurshid, Hira; Salamat, Jmail; Afaque Ali; Ahmad Khan, Waseem; Asim, Muttahhar; Zahid Toor, Sana (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine and compare the diagnostic accuracy of ARISCAT and LAS VEGAS scores in predicting postoperative pulmonary complications (PPCs) in patients undergoing surgery and to determine independent risk factors that are related to PPCs. Study Design: Cross-sectional validation study. Place and Duration of Study: PEMH, Rawalpindi, Pakistan, from Jan to Jun 2025 Methodology: Demographic and clinical data of patients and comorbidities, BMI, type of surgery, and duration of surgery were gathered. PPCs were documented after surgery. ARISCAT and LAS VEGAS scores were computed and dichotomized into low and moderate/ high-risk. Diagnostic performance, sensitivity, specificity, PPV, NPV, and accuracy were taken into consideration when assessing the diagnostic performance. Chi-square test was applied to assess the association between different variables and postoperative pulmonary complications. Results: Out of 186 patients, 78 (41.9) patients developed PPCs. The ARISCAT score had a sensitivity of 74.4%, specificity of 47.2%, PPV of 50.4%, NPV of 71.8%, and overall accuracy of 58.6%. LAS VEGAS score was lower, with a sensitivity of 66.7%, a specificity of 41.7%, a PPV of 45.2%, a NPV of 63.4%, and an accuracy of 52.2%. On bivariate analysis, diabetes mellitus (p = 0.035) and ARISCAT score (p = 0.003) showed a significant association with PPCs, while other variables were not statistically significant (p > 0.05). Conclusion: The ARISCAT score is better than the LAS VEGAS score in predicting PPCs. The inclusion of ARISCAT in perioperative evaluation could help to initially record those patients who can be at high risk and implement preemptive measures.